(untitled) (Research, Society and Development, 2024)
In recent years, a significant increase in suicide cases among adolescents has been seen. At the same time, social networks use has grown, especially among the younger population. This review examined the association of excessive social media use and suicide among adolescents. A bibliographic search of articles, published between 2019 and 2023, was conducted in Pubmed and Science Direct databases using the descriptors “(Social media) AND (suicide) AND (adolescents)” and 26 eligible articles were included. The present study observed that even though social networks facilitates adolescents’ access to psychological help, excessive use is related to an increase in psychiatric comorbidities and can influence suicide through various mechanisms such as cyberbullying, cybervictimization, stimulation of self-mutilation and the publication of videos or images depicting lethal means of suicide.